Reproductive disorders affecting 21-month-old bulls assessed by andrological examination - de Oliveira, Ana Paula Luiz [UNESP]; Lobo, Adalfredo Rocha; de Castilho, Erick Fonseca; Guimarães, José Domingos; Melo, Thiago Vasconcelos; Mota, Diego Azevedo; Siqueira, Jeanne Broch (Universidade Estadual de Londrina, 2020)
The objective of this study was to identify the prevalence of the main pathologies that affect the genital organs of young bulls. We used a database that contained data for 6,408 young Nelore bulls. The data were collected from June to August 2004 and 2005. The bulls were evaluated by andrological examination and semen samples were collected with the aid of an electroejaculation device. The animals were classified in terms of their sexual maturity as animals suitable for reproduction, animals suitable for reproduction in terms of natural service, animals temporarily unfit for reproduction, and animals excluded from reproduction. The reproductive disorders recorded in the excluded animals were classified as penile, testicular, anterior or posterior limb, epididymal, spermatic cord, spermatic, anal sphincter, foreskin, systemic, and seminal vesicle alterations. We used descriptive statistics and analysis of variance to analyze the data. Of the 6,408 bulls evaluated, 309 animals were excluded from reproduction (4.82%). The majority of the excluded bulls (31.7%) suffered from testicular-related pathologies (testicular asymmetry, small scrotal circumference for their age, orchitis, and hydrocele (64.28%, 32.65%, 2.04%, and 1.02%, respectively), seminal vesicle alterations (31.39%), sperm defects (17.15%), and penile alterations (6.79%). Of the 309 animals excluded from reproduction, 21 (6.79% of the excluded and 0.32% of the total animals) suffered from some type of penile alteration, such as persistence of the frenulum (16/21) and total or partial penile adhesion (5/21). Confining the herd for two months and subjecting the animals to their first andrological examination at a younger than usual age, with the objective of selling them, could be why there were high incidences of seminal vesicle pathologies (owing to the homosexual behavior of the males) and of penises with high adhesion rates, which are characteristic of animals that have not yet entered puberty. In general, the low percentage of animals excluded from reproduction in the studied herd indicates the adequacy of the selection program.
Afecções reprodutivas que acometem tourinhos (21 meses) avaliados por meio de exame andrológico
Keywords: Bovines; Pathologies; Reproduction